RUNTUHNYA INSTITUSI MAHKAMAH AGUNG (THE INDONESIAN SUPREME COURT: A STUDY OF INSTITUTIONAL COLLAPSE) - Akbari, Anugerah Rizki (Indonesia Law Review, 2013)
Since the fall of Indonesian president Soeharto, a major focus of the reformers has been the corrupt and inefficient judicial system. Within the context of a history of the Supreme Court in post-independence Indonesia, Sebastiaan Pompe analyzes the cause of the judiciary’s failure over the past decades. This book provides an essential background for those seeking to understand why legal reform has been so slow and frustrating in the post-1998 period.